Therapeutic approach to the iatrogenic invasive mole – A report of two cases - Rakić, Aleksandar; Nikolić, Branka; Radojičić, Ognjen; Džuverović, Marko (Vojnosanitetski pregled, 2022)
Introduction. Invasive mole, a form of gestational trophoblastic neoplasia (GTN), is defined as penetration of molar tissue into the myometrium and/or presence of extra-uterine metastases. An invasive mole arising from a complete hydatidiform mole is more common than an invasive mole arising from the partial hydatidiform mole. Dilatation and uterine evacuation and/or curettage (D&E/C) is the first step in managing molar pregnancy. Uterine perforation is the most serious complication of this procedure. A less common one is the false passage. Case report. The first case report describes a 47-year-old woman who was referred to our Clinic under the suspicion of GTN, with elevated serum beta human chorionic gonadotropin (beta hCG) levels. Intraoperatively, devitalized ovular tissue arising from the uterine perforation was observed. Histopathological exam (HPE) of tissue obtained from hysterectomy confirmed an invasive mole as a result of uterine perforation made during D&E/C. The second patient, a 32-year-old woman with vaginal bleeding, nausea, and high levels of serum beta hCG levels was admitted to our Clinic. After four D&E/C, and persistently high levels of serum beta hCG levels, explorative laparotomy has been performed. A false passage created during D&E/C with necrotic and molar tissue was observed. The partial hydatidiform mole was confirmed by the HPE. Conclusion. This is the second reported case in the literature of postmolar GTN as a result of iatrogenic perforation of the uterus, and also the first described case of postmolar GTN arising from a false passage, created as an iatrogenic complication of D&E/C. A national survey of iatrogenic events during the treatment of gestational trophoblastic disaeses is needed since these events could completely change the therapeutic strategies in managing these diseases.